Electrochemical synthesis of functional nanowires - Fawzy, Mirette (Department of Physics, 2016)
Semiconducting, metal, and multi-segmented nanowires of 200 nm diameters with lengths up to 10_m were synthesized through electrochemical deposition in the pores of anodic aluminium oxide (AAO) and polycarbonate track-etched (PCTE) templates. With the work focusing on CdSe nanowires, results from the cyclic electrodeposition/stripping method was reported with different deposition conditions(potential range, solution, and scan rate). The stoichiometric deposition of CdSe nanowires was confirmed by energy dispersive spectroscopy (EDS) analysis, with an average Cd:Se atomic percentage of0.92. Structural characterizations were done on the synthesized nanowires via scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD) measurements. Devices with a single CdSe nanowire were made by standard electron beam lithography techniques. Electrical transport measurements were performed on the nanowire arrays as well as single contacted CdSe nanowires. Photo response measurements were also carried out on the samples in the dark and under illumination. The nanowire arrays showed pronounced visible light photoconductivity. As a direct application, a preliminary proof-of-concept photoelectrochemical activity test for water splitting using the synthesized CdSe nanowires was performed in a water/methanol mixture.